Genetic Evidence Reveals Distinct Lineage of Chinese Pangolin in Nepal: Insights From Scat and Blood Samples for Conservation and Wildlife Forensics - Fiona Hogan; Faye Wedrowicz; Ambika Pd. Khatiwada; Janardan Dev Joshi; Sam Wasser; Wendy Wright (Ecology and Evolution)
ABSTRACT Pangolins face critical threats from illegal trade and habitat loss, making their conservation a global priority. Despite their ecological and conservation significance, these elusive creatures remain poorly understood, particularly regarding their phylogeography and genetic diversity. This study successfully isolated DNA from two types of pangolin scat samples (whole scat and swabs) and blood that had been stored frozen for up to 3 years. A mitochondrial cytochrome b (424 bp) sequence was reliably generated from both types of scat samples, irrespective of whether the scat appeared in ‘good’ or ‘poor’ condition at the time of collection, and from the blood samples. Sanger sequencing identified four novel cytochrome b haplotypes, with distinct variations observed across sampling regions in Nepal (central and east). A comparison with reference sequences from China, Taiwan and Thailand revealed that the Chinese pangolins in Nepal represent a genetically distinct variant, differing by 15–19 base pairs from these other populations. These findings underscore significant genetic differentiation of Chinese pangolins in Nepal, with implications for the species' conservation and management. The methods described in this study are robust and adaptable, offering a valuable framework for broader genetic studies of pangolin populations across Nepal. Such approaches could facilitate the genetic mapping of pangolin variations, aiding in the identification of significant populations, the evaluation of conservation interventions and forensic applications to combat illegal poaching. This work emphasises the critical role of genetics in understanding and protecting pangolins, offering insights that are vital for their long‐term conservation.